Synthesis, Characterization and Electrocatalytic Activity of Bi- and Tri-metallic Pt-Based Anode Catalysts for Direct Ethanol Fuel Cells - D'Urso, C. (2012)
Three Pt-based anode catalysts supported on Vulcan XC-72R (VC) were prepared by using a modified polyol process. These materials were characterized and tested by X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF) and Transmission Electron Microscopy (TEM). XRD and TEM analysis indicated that especially the ternary anode catalysts consisted of uniform nanosized particles with sharp distribution. The Pt lattice parameter was smaller, in the ternary PtSnIr catalyst whereas it increased with the addition of Sn and Rh, in the corresponding binary and ternary catalysts. Cyclic voltammetry (CV) measurements showed that Sn, Ir and Rh may act as promoter of Pt enhancing ethanol electro-oxidation activity. It was found that the direct ethanol fuel cell (DEFC) performances were significantly improved with these modified anode catalysts. This effect on the DEFC performance is attributed to the so-called bi-tri-functional mechanism and to the electronic interaction between Pt and additives. The performance increased significantly with the temperature. However, it was also possible to observe some decay with time for all catalysts due to the formation of surface poisons, probably consisting in CO-like species. At 60 °C, the PtSnIr catalyst showed the best performance, as a result of a proper morphology and promoting effect